Unification of Gravity and Electromagnetism - Weinstock, Daniel (Eximia, 2023)
A new beginning of this paper is the ideas on unified field theory ‘ which is 9inspired by ideas on Quantum gravity. This is the formula : 8pi is the Gamma at (5) dimensions ik tensor notation to phi which is the metric tensor and barred phi which is the covariant tensor using the partial derivative and it’s chain rule for both phi and barred phi . the first metric phi has the 2 order ik and the barred phi jk ; this equals Gamma (5) dimensions for both phi’s which is containing the phi tensor ij and barred phi jk order 2 Each one. _ minus Gamma (5) dimensions ik metric phi jk divided by 2. This part now is developed from a paper in the bulliten journal and l have given the footnotes later on in the paper. L have been inspired (but not copied exactly ) einsteins unified theory and General Relativities main equations for it has inspired me and a hve a proof of it in my notes.